Cover, Content, and Editorial Note from Borneo J Pharm Vol. 7 No. 2 May 2024 - Borneo J Pharm, Chief Editor of (Borneo Journal of Pharmacy, 2024)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm), has been published in May 2024. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, Clinical-Community Pharmacy, and Management Pharmacy. This edition includes writings from five countries: Indonesia, Malaysia, Nigeria, Sierra Leone, and Uganda. The authors come from several institutions, including Institut Teknologi Bandung, Universitas Darussalam Gontor, Universitas Koperasi Indonesia, Universitas Lambung Mangkurat, Universitas Muhammadiyah Prof. DR. HAMKA, Institut Pertanian Bogor, Biomatics Indonesia, Indonesian Institute of Bioinformatics, Universitas Nasional, University of Ilorin, Summit University, Ambrose Alli University, Mbarara University of Science and Technology, Kampala International University, Premium Medical Services, Kebbi State University of Science and Technology, Clarke International University, Universitas Muhammadiyah Yogyakarta, International Islamic University Malaysia, Universitas Mahasaraswati Denpasar, Universitas Indonesia, National Research and Innovation Agency of the Republic of Indonesia, Menur National Mental Hospital, and East Java Provincial Health Service. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, could re-participate for publication in the next edition on August 2024. Wassalamu’alaikum Wr. Wb.